The Influence of Organizational Culture, Work Environment, and Work Discipline on Employee Performance at The Social Services Office of Medan City - Halawa, Nike Ardila; Adam, Aisyah Azhar (Journal of Business Management, 2025)
Employee performance is one of the benchmarks for government agencies in creating added value by producing goods or services to achieve organizational goals. This study aims to determine and analyze the influence of organizational culture, work environment, and work discipline on employee performance at the Medan City Social Service Office. The population consisted of 50 employees. Data collection techniques in this study were questionnaires, observation, interviews, and pre-surveys. Data analysis was conducted using multiple linear regression and descriptive statistics. The results indicate that organizational culture has a positive and significant influence on employee performance with a significance value of 0.028, work environment has a positive and significant influence on employee performance with a significance value of 0.028, and work discipline has a positive and significant influence on employee performance with a significance value of 0.049. Organizational culture, work environment, and work discipline simultaneously influence employee performance at the Social Affairs Office of Medan City with a significance value of 0.000.